Toughening poly (lactic acid) and aiding the melt-compounding with bio-sourced plasticizers - Tee, Yee Bond; A. Talib, Rosnita; Abdan, Khalina; Chin, Nyuk Ling; Kadir Basha, Roseliza; Md. Yunos, Khairul Faezah (Elsevier, 2014)
The capability of bio-sourced plasticizers epoxidized palm oil (EPO) and epoxidized soybean oil (ESO) in toughening and aiding the melt-processing of PLA were investigated. At various loadings, they were melt-compounded with PLA and hot pressed into 3-mm sheets for impact strength testing. From the torque and stock temperature curves obtained during compounding, both plasticizers rapidly reduced the torque and stock temperature. While EPO readily supports the processing and toughens PLA, higher content of ESO is needed to perform correspondingly. These improvements suggest the potential of using EPO and ESO as plasticizer substitutes which shall contribute in the PLA processing industry.